Case reportsCoronary artery perforation treated with multiple bare metal stent implantation - Baskurt, Murat; Keskin, Kudret; FazlIogullarI, Osman; Ayça, Burak; Kalyoncu, Muhsin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Although coronary artery perforations are quite rare, when they occur, the consequences are devastating. Treatment options differ according to the type, location and severity of the perforation. As a general rule severe perforations are treated with covered stents. However, when implanting a covered stent is not an option as in our case due to various reasons, multiple bare metal stent implantation may be a good option. Besides that, management of the antiplatelet and the anticoagulant therapy remains controversial. We believe that therapy should be individualized.